A new genus and species of Leptopsaltriini (Hemiptera: Cicadidae) from the Agasthyamalais of the Western Ghats in Peninsular India - Kalesh Sadasivan; Vivek Sarkar (Journal of Asia-Pacific Biodiversity, 2023)
A new genus of cicada, Sahyaterpnosia gen. nov., is described from the subtropical hill forests of southern Western Ghats of Peninsular India. We place the genus in the tribe, Leptopsaltriini Moulton, 1923. The genus can be distinguished from all other genera in Leptopsaltriini by the following combination of characters: hindwing with six apical cells; timbal cover minute, abdominal sternites III & IV without tubercles; posterior margin of male tergite III, wider than mesonotum; basal lobe of pygofer lobes, ill-defined, substantially confluent with pygofer margin, and thick aedeagus with a characteristic spine on its tip on dorsum. The new species, Sahyaterpnosia laevospina sp. nov., is designated as a type of this genus and is characterized by the male genitalia with thick aedeagus bearing a characteristic spine on its tip on the dorsum on the left side.